2021
DOI: 10.1111/nph.17653
|View full text |Cite
|
Sign up to set email alerts
|

DE‐ETIOLATED1 has a role in the circadian clock of the liverwort Marchantia polymorpha

Abstract: Previous studies of plant circadian clock evolution have often relied on clock models and genes defined in Arabidopsis. These studies identified homologues with seemingly conserved function, as well as frequent gene loss. In the present study, we aimed to identify candidate clock genes in the liverwort Marchantia polymorpha using a more unbiased approach.To identify genes with circadian rhythm we sequenced the transcriptomes of gemmalings in a time series in constant light conditions. Subsequently, we performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 91 publications
1
14
0
Order By: Relevance
“…The enlarged thallus was maintained throughout the adult life of the loss-of-function lines, and was also observed after 6 weeks of growth in long day photoperiod (LD) ( Fig 1B and 1C ). Growth rate analysis, measuring the observable thallus area of gemmalings from wild type and the amiR-lines ( Fig 1D ), showed that the highly efficient EF1 pro : amiR- Mp EFL Mp MIR160 construct, reducing Mp EFL mRNA levels with >90% [ 35 ], resulted in growth rates significantly higher than both EF1 pro : amiR- Mp LUX Mp MIR160 and wild type ( P < 2x10 -16 ; Fig 1E ). Plants harboring the less efficient EF1 pro : amiR- Mp LUX Mp MIR160 construct (>60% lower mRNA levels compared to wild type) [ 35 ] displayed growth rates significantly higher than wild type but lower than EF1 pro : amiR- Mp EFL Mp MIR160 ( P < 2x10 -16 ; Fig 1E ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The enlarged thallus was maintained throughout the adult life of the loss-of-function lines, and was also observed after 6 weeks of growth in long day photoperiod (LD) ( Fig 1B and 1C ). Growth rate analysis, measuring the observable thallus area of gemmalings from wild type and the amiR-lines ( Fig 1D ), showed that the highly efficient EF1 pro : amiR- Mp EFL Mp MIR160 construct, reducing Mp EFL mRNA levels with >90% [ 35 ], resulted in growth rates significantly higher than both EF1 pro : amiR- Mp LUX Mp MIR160 and wild type ( P < 2x10 -16 ; Fig 1E ). Plants harboring the less efficient EF1 pro : amiR- Mp LUX Mp MIR160 construct (>60% lower mRNA levels compared to wild type) [ 35 ] displayed growth rates significantly higher than wild type but lower than EF1 pro : amiR- Mp EFL Mp MIR160 ( P < 2x10 -16 ; Fig 1E ).…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that M . polymorpha gemmalings are not expanding in constant darkness and therefor this growth condition was not tested [ 35 ]. Under SD conditions we found a limited, but significantly, higher growth rate in two independent Mp pif ko mutant as compared to two restored lines (statistical analysis gave a P < 10 −15 for equal slopes).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other reporters for circadian rhythms in M. polymorpha are also less robust than in flowering plants. For example, rhythms of some promoter-luciferase reporters damp quite rapidly and present a range of periods across replicates, with this difference in robustness evident when circadian rhythms in M. polymorpha and Arabidopsis are compared (Lagercrantz et al 2021, Linde et al 2017) (Dataset S1). This desynchronization of replicate thalli is reminiscent of the phase desynchronization that occurs between the rhythms of individual cells in the leaves of Lemna gibba under free running conditions, compared with the maintenance of phase synchrony in L. gibba under zeitgeber cycles (Muranaka and Oyama 2016).…”
Section: Discussionmentioning
confidence: 99%
“…M. polymorpha is thought to have diverged from flowering plants about 400 million years ago (Delwiche and Cooper 2015, Kohchi et al 2021), with liverwort-like plants occurring earlier in the fossil record than other land plant forms such as vascular plants (Edwards et al 1995). M. polymorpha is a useful model to investigate questions concerning the evolution of circadian regulation because it has a circadian oscillator that shares some components with flowering plants (Lagercrantz et al 2021, Linde et al 2017), there is circadian regulation of a subset of the transcriptome and the position of its thallus lobes (Lagercrantz et al 2021, Lagercrantz et al 2020), and it can be used in experimental designs comparable to models such as Arabidopsis. Whilst circadian rhythms and some aspects of circadian clock structure have been identified in M. polymorpha , it is not yet known whether the regulation of photosynthesis represents a conserved output from its circadian system.…”
Section: Introductionmentioning
confidence: 99%